On the Responses of Braced Diaphragm Wall Supporting Deep Excavation Subjected to Asymmetric Surcharge Loads - Recep Akan (Advances in Civil Engineering)
As cities grow, so does the need for housing and transportation infrastructure, necessitating deep excavations. Near the deep excavation, especially in the urban centers, there are existing structures whose loads are often different, resulting in asymmetric loading of the excavation system and different behavior on each side of the excavation. In this study the strut forces, lateral deformations, bending moments on each wall, as well as the settlements and heaves of the soil behind both walls in the asymmetrically loaded strut-supported excavation system are determined using the finite element method (FEM). The analyzes are performed using Plaxis 2D v20, a computer software based on the FEM. In addition, regression analyses are performed on the results, and correlations that predict the relevant results depending on the surcharge loads are presented.